ENSURING THE ECONOMIC SECURITY OF ENTERPRISES NETWORK STRUCTURES: PROJECT CONTEXTSм (Development Service Industry Management, 2023)
The article examines the concept of economic security, as well as substantiates the practical of ensuring the economic security of network structures using a project approach. On the basis of which, the ratio of the main components of economic security enterprises network structures in the context of project aspects is proposed. A comprehensive study of ensuring the economic security network structures was conducted. The algorithm for strengthening the security component of enterprise network structures with the identification of the relevant stages is substantiated.
Keywords: enterprises of network structures; economic security; project approach; structure of enterprises; mechanism of formation economic security